2022
DOI: 10.3389/fncel.2022.949521
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the research trends of astrocytes in stroke: A bibliometric analysis

Abstract: BackgroundStroke, including ischemic stroke and hemorrhagic stroke, possesses complex pathological mechanisms such as neuroinflammation, oxidative stress and blood-brain barrier damage. Astrocyte functions have been reported during injury, neuroprotection and cell crosstalk. It plays a key role in exacerbating stroke injury, promoting neurological repair and enhancing neuroregeneration.AimThis holistic bibliometric analysis aimed to provide a general overview of the recent advancement and the hotspots in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Data collection WOS core collection database is one of the most comprehensive, systematic and authoritative databases, containing over 13000 internationally recognized in uential academic journals that have been widely used for bibliometric analysis [19,20]. We referred to previous publications and developed search strategies related to oxidative stress and ischemic stroke (Table S2) [21,22]. Inclusion and exclusion criteria are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection WOS core collection database is one of the most comprehensive, systematic and authoritative databases, containing over 13000 internationally recognized in uential academic journals that have been widely used for bibliometric analysis [19,20]. We referred to previous publications and developed search strategies related to oxidative stress and ischemic stroke (Table S2) [21,22]. Inclusion and exclusion criteria are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis is a statistical tool that provides an overview of a specific scientific research field, describes the research trends, and predicts the prospective future directions through qualitative and quantitative approaches [20]. In recent years, bibliometric analysis has been extensively used in stem cell research and the field of neuroscience [21][22][23]. In this study, we performed a bibliometric study of the literature on stem cells and ischemic stroke published between 2001 and 2022.…”
Section: Ivyspringmentioning
confidence: 99%
“…As a type of neurological disease, stroke is the second major cause of death and a key contributor to disability-adjusted life years (DALYs). Approximately 101.47 million stroke events occurred globally in 2019, 12.2 million of which were new cases 3 . Studies have confirmed neurodegeneration secondary to stroke, which can cause progressive neuronal loss, cognitive and motor dysfunction, and ultimately dementia [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%